Steam reforming of toluene: Impacts of externally added oxygen-containing intermediates on property of coke. (19th May 2023) - Bkangmo Kontchouo, Félix Mérimé; Fan, Mengjiao; Inkoua, Stelgen; Sun, Yifan; Zhang, Shu; Hu, Xun
Abstract: Toluene is a typical tar compound resulting from biomass gasification. Toluene reforming could generate abundant carbonaceous intermediates that easily aggregate to form coke. Herein, the co-reforming of toluene with methanol or formic acid is conducted, aiming to understand impacts of oxygen-containing intermediates from dissociation of methanol or formic acid on coking tendency and properties of coke formed. The results indicated that the coke percentage in the used catalyst from 34.7% in toluene reforming to 14.7% with co-addition of formic acid while 22.3% with addition of methanol. This results from presence of abundant oxygen-containing intermediates (COx and ∗ OH) generated from the dissociation of methanol or formic acid, which effectively gasify the C=C species from toluene. Additionally, dissociation of formic acid generates intermediates bearing the C=O functionality that involve in polymerization, forming amorphous coke of aliphatic nature and high tendency to oxidation, which is opposite to that of co-feeding methanol. Highlights: Co-reforming of toluene/methanol mitigates coking and enhances catalytic stability. ∗COx and ∗OH from methanol gasify with ∗C=C and =CHx species from toluene. Co-reforming of toluene/formic acid deactivates catalyst by forming aliphatic coke. Formic acid dissociates to intermediates with C=O that involves in polymerization. O-containing species from co-reforming impacts morphology and hydrophilicity of coke.